1990
DOI: 10.1007/bf02897205
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic function in anthracycline-treated breast cancer patients

Abstract: Preclinical studies suggest that in addition to the well-known direct damage to the myocardium, anthracycline antineoplastic drugs exert toxic effects on the cardiovascular autonomic system as well. To investigate whether this phenomenon occurs in the clinic, we carried out noninvasive, widely used tests of cardiovascular autonomic physiology in 55 women with stage II or III breast cancer. In all, 31 were being treated with anthracycline-containing chemotherapy regimens, and 24 who were receiving CMF (cyclopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Effects of anthracycline therapy on HRV in humans have been reported previously [29][30][31][32][33]. Three of these studies were retrospective [29,31,32], and one study evaluated cardiac parasympathetic control [30].…”
Section: Discussionmentioning
confidence: 96%
“…Effects of anthracycline therapy on HRV in humans have been reported previously [29][30][31][32][33]. Three of these studies were retrospective [29,31,32], and one study evaluated cardiac parasympathetic control [30].…”
Section: Discussionmentioning
confidence: 96%
“…Mean heart rate level is linked with physical activity which may play an important role in lowering the risk to die of cancer. As far as we know, relationships between heart rate variability and cancer have only been reported analysing the influence of paclitaxel chemotherapy (Ekholm et al ., 2000) or of anthracycline treatment (Viniegra et al ., 1990). On the other hand, a large number of studies can be found demonstrating that circadian physiological rhythms are altered in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate dynamics in diabetes and breast cancer · H. Bettermann et al ...................................................................................................................................................................................................................................................................................................................... ..... important role in lowering the risk to die of cancer. As far as we know, relationships between heart rate variability and cancer have only been reported analysing the in¯uence of paclitaxel chemotherapy (Ekholm et al, 2000) or of anthracycline treatment (Viniegra et al, 1990). On the other hand, a large number of studies can be found demonstrating that circadian physiological rhythms are altered in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of anthracycline therapy on HRV in humans have been reported previously [29][30][31][32][33]. Three of these studies were retrospective [29,31,32], and one study evaluated cardiac parasympathetic control [30]. In the study by Postma et al [31] an increase in LF components and a decrease in HF components of HRV were observed in children treated with higher cumulative doxorubicin doses exceeding 400 mg\m#.…”
Section: Discussionmentioning
confidence: 94%